2023
DOI: 10.1111/jan.15751
|View full text |Cite
|
Sign up to set email alerts
|

Nursing in a prison context: A focused mapping review and synthesis of international nursing literature

Abstract: AimTo provide a snapshot of the extent to which nursing and the prison context features in non‐specialist/generic nursing journals.DesignFocused mapping review and synthesis.MethodsRelevant articles were examined for the extent to which they featured nursing and the prison context. A descriptive and contextual analysis of the data was carried out to provide a topography and synthesis of the key trends identified.Data SourcesArticles meeting criteria for nursing and the prison context in relevant non‐specialize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(144 reference statements)
0
2
0
Order By: Relevance
“…Health disparities among different demographic groups continue to be a significant challenge in healthcare and a growing area of interest.Nursingresearchisincreasinglyfocusedonidentifyingtheroot causes of health inequalities and developing targeted nursing interventions to address them. For example, included in this special issue are studies about vulnerable populations including prisoners (Bright et al, 2023), abused women (Halldorsdottir, 2023) and those experiencing housing instability (Robinson et al, 2023). From the perspective of female survivors, Halldorsdottir (2023) looked at the impact male intimate terrorism had on survivors.…”
Section: Under S Tudied He Alth Dis Paritie S and V Ulner Ab Le P Opu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Health disparities among different demographic groups continue to be a significant challenge in healthcare and a growing area of interest.Nursingresearchisincreasinglyfocusedonidentifyingtheroot causes of health inequalities and developing targeted nursing interventions to address them. For example, included in this special issue are studies about vulnerable populations including prisoners (Bright et al, 2023), abused women (Halldorsdottir, 2023) and those experiencing housing instability (Robinson et al, 2023). From the perspective of female survivors, Halldorsdottir (2023) looked at the impact male intimate terrorism had on survivors.…”
Section: Under S Tudied He Alth Dis Paritie S and V Ulner Ab Le P Opu...mentioning
confidence: 99%
“…From the perspective of female survivors, Halldorsdottir (2023) looked at the impact male intimate terrorism had on survivors. Halldorsdottir (2023) concluded that nurses need to be aware of the danger and be able to screenforintimateterrorism.Nursesneedtohavetheknowledge and skills to be able to provide trauma-focussed care to women who have been victims of such trauma (Halldorsdottir, 2023).Amapping and review synthesis conducted by Bright et al (2023) provided a snapshot of how sporadically articles in relation to nursing in the prison context are published in nonspecialist/generic nursing journals highlighting the necessity for increasing publication of nursing in the prison context with the aim of reducing stigma and marginalization of prisoners or people working in prisons (Bright et al, 2023). Robinson et al (2023) described how pregnancy health among birthing and postpartum people is impacted by housing instability.…”
Section: Under S Tudied He Alth Dis Paritie S and V Ulner Ab Le P Opu...mentioning
confidence: 99%